1996
DOI: 10.1007/bf00224038
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of chromosomes in anaphase cells in embryogenic callus cultures of maize (Zea mays L.)

Abstract: Mitotic anaphase cells of highly friable and embryogenic calluses which had been induced from immature embryos of two inbred lines of maize that have contrasting levels of heterochromatic knobs were analysed for the presence of abnormalities 3, 6, 9 and 12 months after the initiation of culture. A total of 500 typical anaphases was scored at each time point, and various aberrations, such as delay in the separation of sister chromatides, chromosome bridges (single, double and multiple) and chromosome fragments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Several studies on regenerated plants have shown frequent occurence of chromosome breakage in plant tissue culture and that breakpoints are often associated with late-replicating heterochromatic regions (Phillips et al, 1994). Normal cell cycle controls are presumed to be disrupted in the culture environment leading to the formation of chromosome bridges, due to the delayed separation of sister chromatids at heterochromatic regions (Fluminhan and Kameya, 1996). Since chromosome fragments were noticed only in a few cells (Figure 2h), observed anaphase and telophase bridges probably result from stickiness.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies on regenerated plants have shown frequent occurence of chromosome breakage in plant tissue culture and that breakpoints are often associated with late-replicating heterochromatic regions (Phillips et al, 1994). Normal cell cycle controls are presumed to be disrupted in the culture environment leading to the formation of chromosome bridges, due to the delayed separation of sister chromatids at heterochromatic regions (Fluminhan and Kameya, 1996). Since chromosome fragments were noticed only in a few cells (Figure 2h), observed anaphase and telophase bridges probably result from stickiness.…”
Section: Resultsmentioning
confidence: 95%
“…Cytologically aberrant plants in maize have also been reported by Edallo et al (1981). Further, delays in the separation of sister chromatids, chromosome bridges, and chromosome fragments were found to occur extensively in embryogenic cultures of maize (Fluminhan and Kameya, 1996). Karp and Maddock (1984) detected substantial changes in both chromosome number and structure in plants of four different wheat (Triticum aestivum 2n 6x 42) cultivars regenerated via somatic embryogenesis.…”
Section: Identification Of Somaclonal Variation In Micropropagation Smentioning
confidence: 96%
“…In the context of organized meristem culture-derived plants, the present understanding is that short-term somatic embryogenesis and/or enhanced axillary branching cultures (McCoy et al, 1982;Lee and Phillips, 1987a,b;De Buyser et al, 1988;Vasil, 1994;Fluminhan and Kameya, 1996;Henry et al, 1996;Brar and Jain, 1999) from particular genotypes (Zehr et al, 1987;Bebeli et al, 1988;Khalid et al, 1989;Morrish et al, 1990), preferably diploid in constitution, can increase the genetic fidelity of micropropagated plants.…”
Section: Factors Influencing Somaclonal Variationsmentioning
confidence: 97%
“…Cytological variations were evident for all tested species (Karp and Maddock, 1984;Karp er al., 1987;. Delays in the separation of si ster chromatids, chromosome bridges and chromosomal fragments were demonstrated to occur extensively in embryogenic cultures of maize (Fluminhan and Kameya, 1996). Delays in the separation of si ster chromatids, chromosome bridges and chromosomal fragments were demonstrated to occur extensively in embryogenic cultures of maize (Fluminhan and Kameya, 1996).…”
Section: Cytological Changesmentioning
confidence: 99%
“…Extensive experimental results make unlikely the suggestion that the frequency of abnormal chromosome complements is reduced in wheat somatic-embryo-derived plants (Henry er al., 1996). Thus, increased duration of in-vitro culture, past 90-120 days, has been associated with increased cytogenetic variation in regenerated plants of maize (Lee and Phillips, 1987a;Fluminhan and Kameya, 1996), oat (McCoy er al., 1982), wheat (De Buyser er al. Thus, increased duration of in-vitro culture, past 90-120 days, has been associated with increased cytogenetic variation in regenerated plants of maize (Lee and Phillips, 1987a;Fluminhan and Kameya, 1996), oat (McCoy er al., 1982), wheat (De Buyser er al.…”
Section: Cytological Changesmentioning
confidence: 99%